Antioxidant, Antimicrobial Potential and Phytochemical Attributes of Impatiens edgeworthii - Mushtaq, Muhammad; Anwer, Nadeem; Asim Waqar, Muhammad; Latif, Shabanem; Ali Shahid, Shaukat; Azam, Adeela (Asian Journal of Chemistry, 2013)
In this work, we investigated the availability of antioxidant, antimicrobial and phytochemical agents native to Impatiens edgeworthii in various extraction solvents. The fractional extracts obtained for different solvents showed substantial levels total phenolic (124-430 mg/g GAE), anti-radical potential (32-89 %) and total antioxidant capacity 0.3-0.8 versus gallic acid and butylated hydroxy toluene having total antioxidant capacity value 0.85-1.2. Phytochemical analysis confirmed the presence of flavonoids, sugars, alkaloids and saponins. in vitro disc diffusion assay showed that all the extracts of I. edgeworthii have the antimicrobial activity comparable with standard antibiotics. Furthermore, among tested solvents (n-hexane, chloroform, ethyl acetate and methanol) ethyl acetate was found to be more effective for the recovery of phytochemicals, phenolics, antioxidants and antimicrobial agents. The results of present study indicate I. edgeworthii is latent source of potential bioactive and might be further explored for the development of chemopreventive drugs and nutraceuticals.